Acoustic correlates of phonetic corection - Mildner, Vesna (Array, 2001)
The paper addresses the question of speech correction using the auditory-phonetic approach. This approach is based on developing good auditory perception of the spoken material, by manipulating the signal itself, and by various strategies including the use of the optimal sound context, word and sentence position, intonation and stress patterns, and movement accompanying speech production. The acoustic analysis and listening judgements of speech produced by the same subject before and after phonetic correction indicate significant improvement in pronunciation. This type of correction may be used from speech-hearing pathology to foreign language learning.